2017
DOI: 10.1111/acer.13519
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Feeding in Mice Promotes Colonic Hyperpermeability and Changes in Colonic Organoid Stem Cell Fate

Abstract: Background Alcohol increases intestinal permeability to pro-inflammatory microbial products that promote liver disease, even after a period of sobriety. We sought to test the hypothesis that alcohol affects intestinal stem cells using an in vivo model and ex vivo organoids generated from jejunum and colon from mice fed chronic alcohol. Methods Mice were fed a control or an alcohol diet. Intestinal permeability, liver steatosis/inflammation, and stool short chain fatty acids (SCFA) were measured. Jejunum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
(84 reference statements)
3
31
0
Order By: Relevance
“…There is growing evidence indicating that alcohol abuse alters intestinal permeability to toxic substances, although the direct mechanisms are not completely understood. A recent study showed that mice fed an alcohol‐containing diet exhibited decreased apical junctional proteins leading to colonic hyper‐permeability (Forsyth et al ., ). Inflammation may exacerbate barrier dysfunction in a synergistic manner.…”
Section: Discussionmentioning
confidence: 97%
“…There is growing evidence indicating that alcohol abuse alters intestinal permeability to toxic substances, although the direct mechanisms are not completely understood. A recent study showed that mice fed an alcohol‐containing diet exhibited decreased apical junctional proteins leading to colonic hyper‐permeability (Forsyth et al ., ). Inflammation may exacerbate barrier dysfunction in a synergistic manner.…”
Section: Discussionmentioning
confidence: 97%
“…Loss of Wnt signaling in these cells results in loss of secretory lineage epithelial cells and loss of epithelial and crypt structure . Disruption of the Wnt/Notch signaling balance in the ISC results in abnormal changes in stem cell fate ratios and loss of intestinal barrier function (leaky gut) . Targeted loss of Lgr5 results in loss of crypt ISCs and loss of intestinal epithelial renewal .…”
Section: Wnt Signaling In Aging Intestinementioning
confidence: 99%
“…104 Disruption of the Wnt/Notch signaling balance in the ISC results in abnormal changes in stem cell fate ratios and loss of intestinal barrier function (leaky gut). 105,106 Targeted loss of Lgr5 results in loss of crypt ISCs and loss of intestinal epithelial renewal. 98 Inhibiting Wnt signaling in adult mice with an inducible Wnt antagonist, DKK1, blocks proliferation within crypts and results in crypt loss.…”
Section: Wnt Signaling In Aging Intestinementioning
confidence: 99%
“…On the other hand, mice on Lieber-DeCarli (LD) which is an isocaloric liquid diet, go through a similar ramping phase from 0% to 3.395% EtOH (w/v) 21 . To explore chronic alcohol effects, duration of exposure to LD diet is also variable between 25 days to 8 weeks, with an average around one month [22][23][24][25][26][27][28][29] . This model was created to "enhance" the mice ALD phenotype to be similar to the human ALD patient phenotype and to avoid confounding effects of differences in caloric content of oral intake of alcohol consumption.…”
mentioning
confidence: 99%